Determining the annual periodicity of growth rings in seven tree species of a tropical moist forest in Santa Cruz, Bolivia - López, L.; Villalba, R.; Peña-Claros, M. (Forest Systems, 2012)
To determine the annual periodicity of growth rings in seven tree species from a tropical moist forest in Santa Cruz, Bolivia, a fire scar was used as a marker point to verify the annual nature of tree rings. The number of tree rings formed between the 1995 fire scar and the collection of the cross sections in 2002 was visually identified. The seven species showed annual growth rings. In most cases, boundaries between rings were marked by the presence of marginal parenchyma and wall-thicked fibers formed at the end of the growing season. Growth lenses and false rings were recorded in some species. Tree rings can be carefully used in Santa Cruz forests to determine rates of growth. This information is crucial for defining forest management practices in tropical regions.